HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG IMUNISASI DENGAN KELENGKAPAN IMUNISASI DASAR ANAK DI BPM BIDAN SUTARTI, AMD., KEB KOTA MADIUN: Relationship Of Mom's Knowledge Level About Immunization With Complete Children's Basic Immunization In Bpm Bidan Sutarti, Amd., Keb Madiun City - Nisa Ardhianingtyas (LPPM - STIKES Pemkab Jombang, 2019)
Background; Immunization is an effort to provide immunity to infants and children to prevent certain diseases. Based on a preliminary study at BPM Ny. Sutarti, Amd., Keb of 10 mothers who immunized their babies base, in getting (60%) mothers properly immunized their babies and (40%) did not properly immunize their babies. Knowledge of mothers about immunization will affect the implementation of immunization. If the mother's knowledge about giving good immunization is expected to provide immunization to children on schedule. Research purposes; To find out the relationship between the level of knowledge of mothers about immunization and the completeness of basic childhood immunizations. Research methods; Observational analytics with a Cross Sectional time approach to mothers who fully immunize their children, namely 22 people for 2 months. To find out the relationship between the level of knowledge of mothers about immunization and the completeness of basic immunizations of children used the chi square formula. Research result; 14 respondents (63.6%) had high knowledge, 5 respondents (22.7%) were moderate knowledge and 3 respondents were knowledgeable low (13.6%), while respondents gave complete immunizations of 19 respondents (86.4%) and those who did not give a complete immunization of 3 respondent (13.6%). Data analysis using s-quare chi with p value = 0.410, obtained results of Xcount <Xtabel so that Ho is accepted. Conclusion; Research shows that there is no relationship between the level of knowledge of mothers about immunization and the completeness of basic childhood immunizations.